Numerical Investigation on Damage Scenarios of Vane Trailing Edge Using Thermo-Fluid-Structural Analysis - Karn Jeatrakul; Ditthaphat Tanpradit; Prasert Prapamonthon; Vijayanandh Raja; Zhaoqing Ke (My University, 2025)
Abstract Gas-turbine nozzle vanes are used to increase the velocity magnitude of hot gas exiting the combustor. Thus, the vanes must operate at high turbine inlet temperatures (TITs). Essentially, the higher the turbine inlet temperature, the greater the thermal efficiency and propulsive efficiency. Nonetheless, this situation can cause severe damage to the vane material because of the repeated high thermal loads. Using thermo-mechanical analysis, this paper presents damage scenarios of a nozzle vane’s trailing edge (TE) and their impact on flow and heat phenomena, including mechanical behavior of the vane material. As the upstream process, computational fluid dynamics (CFD) simulation with conjugate heat transfer (CHT) is used to numerically investigate flow physics and heat transfer phenomena. Then, for the downstream calculations, a static structure model for a steady temperature analysis is used. The NASA-MARK II vane profile is used to define vane boundaries in the computational domain. Broken vane TE scenarios are presented in both the streamwise and spanwise directions, with a short, shallow cutback expanding into a long, deep one from 0.1 cm x 1 cm to 0.3 cm x 3 cm. The numerical results are mainly presented and discussed in terms of variations in surface and internal temperatures, as well as von Mises equivalent stress and strain. The damaged TE, according to the findings, has a significant impact on the thermo-mechanical variations of the vane material. This emphasizes the severity of a damaged vane TE if the turbine is still operating without maintenance.
Keywords: Turbomachinery Performance and Optimization; Heat Transfer Mechanisms; Computational Fluid Dynamics and Aerodynamics